Barkagan Zinoviy Solomonovich (on the centenary of his birth) - Pavel A. Vorobyov (Clinical Medicine (Russian Journal), 2026)
The article provides biographical data and assesses the scientific achievements of Corresponding Member of the Russian Academy of Medical Sciences, Professor Zinovy Solomonovich Barkagan. The directions of development of his ideas at present are discussed.